(untitled) (International Association of Biologicals and Computational Digest, 2023)
Bio-enzyme have a multiple functionality like use as bio-fertilizer, reducing contamination of ground water and use as natural detergent. This paper’s objective is to assess the effect of bio-enzyme on biochemical like total Protein content, total Phenol content, total Reducing sugar, Starch and chlorophyll content of fenugreek leaves. Treated fenugreek with 4% bio-enzyme shows, more concentration of biochemical than other dilution of bio-enzyme and control plants.